The subsidy as a repression arm of the mexican state. The Michoacana University during the principalship of Alberto Bremauntz (1963-1966) - Rangel Hernández, Lucio (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
Starting with the presidency of Manuel Ávila Camacho (1940-1946), the Mexican State changed of direction in university education policy with the tendency of introducing the entrepreneurial educational model of the United States, but the Universidad Michoacana de San Nicolás de Hidalgo heir from the cardenista (1934-1940) project of popular and nationalist guidance opposed to adopt it, so upon the arrival of Agustín Arriaga Rivera at the principalship of the entity (1962-1968), the institution suffered repressive actions with the purpose of imposing such a modernizing project on it. This article discusses the permanent and systematic policy of harassment exerted by this ruler on the University, using the freezing of its budget as the main instrument of coertion, but it was also understood in the co-optation of the student leaderships and the Porriles practices of a group of infiltrated shock among the university students. It also refers to the struggle that the Nicolaitans fought during Alberto Bremauntz's rectory, to defend the aforementioned popular and nationalist principles upheld by their University.